Artificial Intelligence and Parent Perception: Their Influence on Students’ English Pronunciation Skill at SMPN XYZ Pekanbaru - Julanos, Julanos; Rahmi, Hanifatul; Wiroto, Noto; Sari, Febrina; Hakim, Darul; Baroqah, Ummul (Universitas Pahlawan Tuanku Tambusai, 2025)
Fluency in English requires accurate pronunciation. Many students still have difficulty pronouncing words and sentences correctly, making it hard for listeners to understand. In recent years, artificial intelligence (AI) has witnessed the emergence of numerous applications and platforms, including ChatGPT, ELSA Speak, Memrise, and Duolingo, among others. The success of artificial intelligence (AI) in educational settings is not contingent solely on the students and the technology itself; it is also essential to comprehend the parents' perceptions. This research is correlational. The objective of this study is to investigate the influence of artificial intelligence (AI) and parental perceptions on students' pronunciation skills at SMPN XYZ Pekanbaru. The sample population comprised 166 ninth-grade students selected at random from a total population of 285. The validity and reliability of the questionnaires were tested before distribution to determine how students use AI and how parents perceive it. The students underwent a brief reading test to assess their pronunciation. The findings of this study demonstrate a substantial influence of both artificial intelligence and parental perception on students' pronunciation skills; however, the observed effect size was relatively modest. The present study posits that collaboration between teachers and parents is necessary to ensure that artificial intelligence (AI) provides optimal benefits.